Outcome of ureteric stone treatment with tamsulocin - Pandit, Rakesh Kumar; Gupta, Uma Shankar; Magar, Subash Thapa; Jha, Vinay Kumar (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Though medical expulsive therapy for ureteric stones is increasingly used these days, some recent randomized controlled trials have questioned its benefit. This study evaluates the result of treatment of ureteric stones with tamsulosin. Materials and Methods: This prospective study involved ultrasonographically confirmed cases of uncomplicated unilateral ureteric stones. All patients received tamsulocin 0.4 mg daily for 2 to 6 weeks. The primary end point was stone expulsion. The secondary endpoints were the use of analgesics and adverse events. Results: One hundred and sixty two patients completed the study. Ninety seven patients were male and male to female ratio was 3:2. The mean age was 34.9 ± 9.8 (range: 18-71) years. The mean stone size was 6.17 ± 1.68 (range: 3.3-11.2) mm. By the end of 2, 4 and 6 weeks, cumulative stone expulsion rate was 110 (69.1%), 121 (74.7%) and 126 (77.8%) respectively. For the 49 stones of size £ 5 mm, the expulsion rate was 47 (95.9%) by the end of 6 weeks. The expulsion rates for stones of size > 5 - 7 mm, > 7 – 9 mm and ³ 9 mm were 59 (85.5%), 17 (53.1%) and 3 (25%) respectively by the end of 6 weeks. Lower ureteric stones had the highest expulsion rate of 106 (87.6%) by the end of 6 weeks, and the rate was lowest for upper ureteric stones (34.6%). Ten (6.1%) patients required additional analgesics during the course of treatment. Eleven (6.8%) patients complained of mild light-headedness and dizziness which subsided in a few days. Conclusion: Tamsulocin appears to facilitate expulsion of ureteric stones especially the distal ones. The benefit of tamsulocin seems to be maximum for the stones of size up to 9 mm. Further large scale randomized controlled trial should better define the real benefit and more rationale use of tamsulocin in routine clinical practice.